1975
DOI: 10.1148/116.2.405
|View full text |Cite
|
Sign up to set email alerts
|

Postresection Irradiation for Primary Lung Cancer

Abstract: A total of 219 patients with proved lung cancer were studied to determine whether postresection irradiation improves survival. The results showed that postresection irradiation improved survival among patients with hilar and mediastinal lymph-node metastases of all histological types but did not improve survival among patients without node metastases. The authors recommend that patients with resectable lung cancer involving the hilar and mediastinal lymph nodes be treated by a combination of surgery and radiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…More recently, Walsh et al 12 reported local recurrences in 14 of 121 patients (12%) with reas shown by many previous retrospective and prospective studies, [1][2][3][4][5] but also may improve survival for sected Stage III disease. However, these results were reported as crude rates of local recurrence (not actuarpatients with nonsmall cell lung carcinoma with involvement of N2 lymph nodes.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…More recently, Walsh et al 12 reported local recurrences in 14 of 121 patients (12%) with reas shown by many previous retrospective and prospective studies, [1][2][3][4][5] but also may improve survival for sected Stage III disease. However, these results were reported as crude rates of local recurrence (not actuarpatients with nonsmall cell lung carcinoma with involvement of N2 lymph nodes.…”
Section: Discussionmentioning
confidence: 93%
“…
RESULTS.The median follow-up time was 3.5 years for the patients who were alive Hongzhe Li, Ph.D. 4 at the time of the analysis. The surgery alone versus surgery plus TRT groups were 1 Division of Radiation Oncology, well balanced with respect to gender, age, histology, tumor grade, number of Mayo Clinic and Mayo Foundation, Rochester, mediastinal lymph node stations dissected or involved, and involved N1 lymph Minnesota.

node number.

…”
mentioning
confidence: 99%
“…The risk for local recurrence is lower with PORT (25%-35%), as shown in several retrospective studies listed in Table 1 [13][14][15][16][17][18][19]. In most of these studies, there was a historical comparison with patients who had no PORT, so these figures should be interpreted with caution.…”
Section: Studies Evaluating Portmentioning
confidence: 99%
“…UnfortunateReprint requests should be addressed to J. C. Ruckdeschel * Presented in part at the 16th Annual Meeting of the American Society of Clinical Ontology, San Diego, California, May 27, 1980 ly, the majority of patients have more extensive local spread. Pre-operative [30,33], interstitial [14], postoperative [1,12], and primary radiotherapy [23] have been tested as means of improving the surgical cure rates, with marginal success although palliation of symptoms is often achieved. Chemotherapy as the definitive therapy has shown little promise [16].…”
Section: Introductionmentioning
confidence: 99%